Integrative Multitheoretical Counseling: Cognitive Therapy and Experiential-Humanistic Therapy on Depression of Patient with Depressive Disorder - Phawo, Phongphan; Suthithatip, Surin; Chakrabhandu Na Ayutaya, Sarutabhandu (Journal of Phrapokklao Nursing College, Chanthaburi, 2020)
This experimental research aimed to examine the effects of counseling programs on depression among patient with depressive disorder. The participants consisted of 48 patients with depressive disorder receiving services at out-patient department, Sakaeo Rajanagarindra Psychiatric Hospital and were equally divided into four groups; three experimental groups and one control group (12 patients per group). The research instruments included the integration of Cognitive Theory and Experiential-Humanistic Theory counseling program, the Cognitive Theory counseling program, the Experiential-Humanistic Theory counseling program, the Cognitive-Behavioral Theory counseling program, the subjective unit of distress scale, the suicidal assessment form, the mini-mental state examination: Thai version (MMSE-Thai 2002), the psychotic screening form, the demographic questionnaire, and the Beck Depression Inventory (BDI-IA) with the reliability of .86. The implementation and data collection were conducted from January to May, 2018. Statistics used for data analysis included frequency, percentage, mean, standard deviation, and repeated measure ANOVA: one between-subjects variable and one within-subject variable with multiple comparisons by Bonferroni method. The research results revealed that at the post-trial period, the group receiving the integration of Cognitive Theory and Experiential-Humanistic Theory counseling program (the MTP group) had statistically significant lower mean score of depression than those in the group receiving the Cognitive Theory counseling program (the CT group) and the group receiving the Experiential-Humanistic Theory counseling program (the EXP group), but the MTP group had no different mean score of depression from that in the group receiving the Cognitive-Behavioral Theory counseling program (the CBT group). Additionally, at the follow-up period, the MTP group had statistically significant lower mean score of depression than those in the CT group, the EXP group, and the CBT group. This research suggests that health care providers relating to depressive psychotherapy should appropriately apply this integration of Cognitive Theory and Experiential-Humanistic Theory counseling program for reducing depression among people with depression.